Standardisation of Glycosmis pentaphylla (Retz.) DC. – A Homoeopathic drug (Advancements in Homeopathic Research, 2022)
Glycosmis pentaphylla (Retz) DC. is a shrub belonging to the family Rutaceae. Leaves of this plant are used as medicine in Homoeopathy. Leaves are alternate, imparipinnate; leaflets 3-5, aromatic, elliptic oblong, base cuneate, margin entire, petiole short. The surface of the leaf is striated and dispersed with bright dotted oil glands. Leaf is amphistomatic with anomocytic and tetracytic stomata. Midvein is ribbed on both sides. Vascular bundles in midvein are enclosed by sclerenchymatous sheath. Petiole in T.S. is sub spherical with two small lateral ridges on adaxial. Ground parenchyma of petiole is interspersed with oil glands. Medullary rays interrupt the xylem. The pith and ground parenchyma is often interspersed with tanniniferous and crystaline idioblasts. Physico chemical parameters of raw drug viz. extractive values, ash values, formulation, besides weight per ml, total solids, alcohol content, along with UV absorption and TLC studies have been worked out for mother tincture.
Keywords: pentaphylla; biliary; gastric; jaundice